Parents’ attitude to education of children in Children’s and Youth Sports School - Mazin, V.N. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to determine the attitudes of parents of young athletes to the educational process in youth. Objectives: to identify the expectations of the respondents in relation to the objectives, factors, key actors of the educational process. Material: parents (n = 22) pupils youth (Zaporozhye). Results : the main objectives of the educational process, parents believe their children purchasing habits for a healthy lifestyle. Just acquisition of skills necessary for socialization. Important goals are the recovery teaching loads and providing meaningful leisure activities for children. Found that the majority of parents are not supported targets educational process to achieve a higher athletic performance. As a result of the factors influencing the educational process called parents of the young athlete communication with the coach and team. Just overcoming their child difficulties encountered in training and competitions. Revealed that parents do not consider the planned educational activities effective factor in the educational process. Conclusions: from the educational process in the Youth parents expect improved health and assist in the socialization of children. Achieving these goals is associated with effective educational work of coaches, sports team influence, through their own efforts of the young athlete.